Occult Pneumonia: An Unusual but Perilous Entity Presenting with Severe Malnutrition and Dehydrating Diarrhoea (Journal of Health, Population and Nutrition, 2010)
A three-month old boy was admitted to the Dhaka Hospital of the International Centre for Diarrhoeal Disease Research, Bangladesh (ICDDR,B), Dhaka, Bangladesh, with the problems of acute watery diarrhoea with some dehydration and suspected dyseletrolytaemia, severe malnutrition, and reduced activity. Occult pneumonia was added to the problem list after demonstration of radiologic consolidation in right upper lung, despite the lack of clinical signs, both on admission and after correction of dehydration. The problem list was further expanded to include bacteraemia due to Staphylococcus aureus when the blood culture report was available. Severely-malnourished children may not exhibit typical clinical signs of pneumonia, and the possibility of existence of such problems should be remembered in the assessment and provision of care to hospitalized young children with severe malnutrition. Key words: Diarrhoea, Infantile; Dehydration; Infant nutrition disorders; Pneumonia; Bangladesh DOI: 10.3329/jhpn.v27i6.4333 J Health Popul Nutr 2009 Dec; 27(6): 808-812